2022
DOI: 10.1007/s12265-022-10210-7
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Cardiopulmonary Resuscitation Guided by End-Tidal Carbon Dioxide—a Porcine Model

Abstract: Extracorporeal membrane cardiopulmonary resuscitation (ECPR) during cardiopulmonary resuscitation (CPR) for selected cases and end-tidal carbon dioxide (ETCO2) could be used to guide initiation of ECPR. Ventricular fibrillation was induced in 12 pigs and CPR was performed until ETCO2 fell below 10 mmHg; then, ECPR was performed. Animals were divided into group short (GShort) and group long (GLong), according to time of CPR. Carotid blood flow was higher (p = 0.02) and mean arterial blood pressure lower in GLo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
4
0
1
Order By: Relevance
“…Notably, 12 hours into VA‐ECMO, lactate/pyruvate ratios and glycerol levels rise in CPR60 animals (Figure S1 ) but not significantly. This finding, also seen in another swine study of ECPR duration, 35 could indicate greater ischemic burden or progression of secondary injury processes 37 despite restoration of circulation. This would support development and use of postcardiac arrest neuromonitoring modalities that measure CBF, autoregulation, and oxygenation in real time, informing clinical management and prognostication.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Notably, 12 hours into VA‐ECMO, lactate/pyruvate ratios and glycerol levels rise in CPR60 animals (Figure S1 ) but not significantly. This finding, also seen in another swine study of ECPR duration, 35 could indicate greater ischemic burden or progression of secondary injury processes 37 despite restoration of circulation. This would support development and use of postcardiac arrest neuromonitoring modalities that measure CBF, autoregulation, and oxygenation in real time, informing clinical management and prognostication.…”
Section: Discussionsupporting
confidence: 60%
“…All animals in both groups suffered severe neurological dysfunction and injury as measured by cerebral mitochondrial respirometry (Figure 4 ), neuropathologic analyses (Table S8 ), and cerebral microdialysis (Table S6 ), consistent with findings from other studies. 35 , 36 Interestingly, the proton gradient and inner membrane were not significantly different from sham animals as evidenced by state 4 o respiration without ATP production, which may suggest functional rather than structural mitochondrial injury. Notably, 12 hours into VA‐ECMO, lactate/pyruvate ratios and glycerol levels rise in CPR60 animals (Figure S1 ) but not significantly.…”
Section: Discussionmentioning
confidence: 84%
“…1 ). 64 , 65 , 66 , 67 , 68 15 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 48 .
Fig.
…”
Section: Resultsunclassified
“…Olander et al exclusively investigated S100B as a neurological biomarker, however, there were no significant differences in S100B levels between different durations of ECPR. 37 Zhang et al demonstrated that the ECPR group had elevated levels of various cerebral inflammatory markers. 15 Wollborn et al’ s 2020 study showed an increased level of glial fibrillary acidic protein (GFAP), ionized calcium binding adapter molecule 1 (Iba1), and heme oxygenase-1 (HO-1).…”
Section: Resultsmentioning
confidence: 99%
“…Presently, extracorporeal cardiopulmonary resuscitation is commonly used, replacing traditional CPR to treat IHCA, and this method can effectively improve the survival rate [3,4]. In a study by Ölander et al [5], the effects of extracorporeal cardiopulmonary resuscitation under various end-tidal carbon dioxide levels were analyzed, and the results were veri ed using animal experiments. The post-resuscitation care for IHCA was analyzed in a study by Girotra et al [6], which included targeted temperature management, early coronary angiography, and comprehensive critical care.…”
Section: Introductionmentioning
confidence: 99%